Analysis of Fast Food Consumption on the Risk of Obesity in School Children - Faradina, Anggia (Journal Nutrizione, 2024)
This study aims to analyze the effect of fast food consumption on the risk of obesity in school children using a qualitative approach through literature studies. Data were obtained from various scientific publications, reports from international health organizations, and relevant national journals in the last five years. The results of the analysis show that the frequency of fast food consumption is closely correlated with an increase in body mass index (BMI) and the prevalence of obesity in children. Factors such as exposure to advertising, school environments close to fast food outlets, and family habits play a major role in shaping these consumption patterns. In addition, low physical activity worsens children's nutritional conditions. Effective prevention strategies include interventions in schools through nutrition education and the arrangement of healthy canteens, restrictions on unhealthy food advertisements to children, and city spatial arrangements that limit the presence of fast food outlets around schools. In conclusion, obesity in children due to fast food consumption is a complex problem that requires a cross-sectoral and collaborative approach to create changes in healthier consumption behavior among school children.